2022
DOI: 10.1021/acs.nanolett.1c04413
|View full text |Cite
|
Sign up to set email alerts
|

In situ Thermal-Responsive Magnetic Hydrogel for Multidisciplinary Therapy of Hepatocellular Carcinoma

Abstract: Current surgical single modality treatments for hepatocellular carcinoma (HCC) were restricted by recurrence, blood loss, significant trauma, and poor prognostic. Although multidisciplinary strategies for HCC treatment have been highly recommended by the clinical guidelines, there was limited choice of materials and treatments. Herein, we reported an in situ formed magnetic hydrogel with promising bioapplicable thermal-responsiveness, strong adhesion in wet conditions, high magnetic hyperthermia, and biocompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…Yan et al. reported the in situ formed magnetic hydrogel using magnetite decorated reduced graphene oxide nanosheets (denoted as FG) and NDP hydrogel with strong adhesion in wet conditions, promising thermal responsiveness for use in biomedical applications, high magnetic hyperthermia, and biocompatibility, leading to efficient HCC multidisciplinary treatment including postoperative treatment and transarterial embolization therapy (Yan et al., 2022 ). The hydrogel's ability to reduce postoperative recurrence was demonstrated in vivo.…”
Section: Hydrogels For Localized Chemotherapy Of Liver Cancermentioning
confidence: 99%
“…Yan et al. reported the in situ formed magnetic hydrogel using magnetite decorated reduced graphene oxide nanosheets (denoted as FG) and NDP hydrogel with strong adhesion in wet conditions, promising thermal responsiveness for use in biomedical applications, high magnetic hyperthermia, and biocompatibility, leading to efficient HCC multidisciplinary treatment including postoperative treatment and transarterial embolization therapy (Yan et al., 2022 ). The hydrogel's ability to reduce postoperative recurrence was demonstrated in vivo.…”
Section: Hydrogels For Localized Chemotherapy Of Liver Cancermentioning
confidence: 99%
“…According to Yan et al., they found that in situ formed magnetic‐responsive hydrogel with good thermal responsiveness enables efficient multidisciplinary treatment of hepatocellular carcinoma (HCC), including postoperative treatment and radiation therapy. [ 35 ] The hydrogel may be able to reduce recurrence rates following surgery when tested in vivo. To demonstrate the hemostatic ability of the thermoresponsive hydrogel, they also performed liver scratch studies and liver tumor resection experiments.…”
Section: Stimuli‐responsive Nanocomposite Hydrogels and Application M...mentioning
confidence: 99%
“…Among these types of triggered click reaction hydrogels that can be used in the liver tissue, most studies have constructed responsive hydrogel materials with potential drug delivery engineering applications, which can form their excellent ability to synthesize hydrogels and retain the properties of drugs in their 3D network without losing mechanical integrity even in the swollen state. [31][32][33][34][35][36] For example, clickable drug-loaded polymer macromolecules such as PEG are mixed with hydrogels to form encapsulated PEG hydrogels through a fast and biocompatible click reaction. [37] The reformulation of different monomers and cross-linking schemes used to prepare the hydrogel will lead to changes in the structure and properties of the nanocomposite hydrogel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al synthesized an in situ formed magnetic hydrogel in response to body temperature, which is composed of iron oxide nanoparticles (Fe 3 O 4 @rGO, denoted as FG), used for hepatocellular carcinoma (HCC) postoperative treatment (Fig. 6 ) [ 115 ]. The addition of FG improved the mechanical properties of the hydrogel.…”
Section: Introductionmentioning
confidence: 99%